ECONOMICS OF THE WILDLIFE TRADE theory and implications for conservation. - Chen, Frederick (ROUTLEDGE, 2025)
This book presents a thorough overview and assessment of the economics of the wildlife trade for scholars and conservationists, requiring only a basic understanding of economic principles.Wildlife conservation and the sustainable extraction of living organisms from the wild for human use are fundamentally tied to issues of resource allocation and economics. Yet, there has been a conspicuous dearth of scholarly contribution that examines the wildlife trade using the theories and analytical tools provided by economists. This book fills this gap by presenting a theoretical framework built on a foundation of microeconomic theory that is used to analyze the trade in wildlife goods, the potential effects of various conservation policies, and the economic forces that govern the workings of the markets for wildlife goods. The focus of the book is on explicating the possible impacts of supply-side policies that have been implemented or proposed to achieve a sustainable level of wildlife extraction. The policies that will be considered include the following: stricter anti-poaching policies; trade bans; and legalizing the sale of alternative sources of supplies such as farmed goods, synthetic substitutes, and accumulated stockpiles. The book discusses how the implementation of these policies could affect the incentives of both the suppliers and buyers of wildlife goods to participate in these markets. It also considers how market structure, market concentration, and asymmetric information can affect the impact of these policies.This book is intended for scholars, practitioners, and policymakers in the field of wildlife conservation who are familiar with basic economics and interested in a rigorous exposition of the economic principles relevant to the study of the wildlife trade.
Keywords: Environmental economics.; Wild animal trade.; Wildlife conservation.; elektronické knihy; electronic books